Metode Hypnotherapy Terhadap Perilaku Belajar Pendidikan Agama Kristen Siswa Kelas X SMAN 1 Tamiang Layang - Sugiyanto, Sugiyanto (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
Hypnoteraphy is carried out because of the behavioral diseases that occur among high school students, such as academic procrastination behavior, boredom, laziness, indifference, lack of attention to lessons, learning feels like a burden. The purpose of this study was to determine student behavior before hypnotherapy and to determine the effect of hypnotherapy on student learning behavior. The research method is quantitative using a one-group pretest-posttest experimental design. Experiments were conducted on 20 students who had learning behaviors that were common among students. The results of the experiments that have been carried out that there is a low value of student learning behavior before therapy, which only gets a score of 40. Whereas after therapy the value is equal to 85. The difference in scores before and after therapy is calculated using a paired sample t-test. The calculation results are shown by the statistical number Sig. (2-tailed) of 0.000 <0.05. This means that it is significant to accept Ha, namely that there is an effect of using hypnotherapy on the PAK learning behavior of Class X students of SMAN-1 Tamiang Layang.